0830 A Pediatric Case of Myoclonic Seizures Precipitating Central Sleep Apnea And Sequences of Periodic Breathing During Sleep. (25th May 2022) - Wisniewski, Benjamin; Witt, Rochelle; Dye, Thomas; Arya, Ravindra; Simakajornboon, Narong
Abstract: Introduction: Myoclonic seizures are known to be influenced by the sleep-wake cycle. Although myoclonic seizures have been shown to alter sleep architecture, little is known about their influence on sleep-disordered breathing. Report of Cases: A 7-year-old male with a history of generalized epilepsy of unknown etiology with absence as well as myoclonic seizures, poor impulse control, and fine motor delay was referred for restless sleep and frequent nocturnal awakenings. A routine electroencephalography (EEG) performed 33 months prior to presentation, at an outside institution, reportedly showed 3.0 Hz generalized frontally dominant spike and wave discharges lasting less than two seconds. Video EEG (vEEG) revealed diffuse bilateral poly-spike and slow wave discharges, predominantly during sleep, and myoclonic seizures with abrupt whole-body jerks. Polysomnography, at this time, was characterized by mild central sleep apnea (AHI: 3.7; OAHI: 0.0; CAI: 2.8; REM AHI: 14.4). His lamotrigine dosing was increased to from 1.8 mg/kg/day to 3.6 mg/kg/day, at presentation, with seizure control for three months but he developed a recurrence of myoclonic seizures in the setting of sleep deprivation. A repeat vEEG was similar to previous findings and his lamotrigine was increased further and clobazam was added. Due to worsening behaviors, clobazam was discontinued and a weaning plan for lamotrigine was formulated. Repeat polysomnography demonstrated worsening central sleep apnea (AHI: 18.3, OAHI: 2.3), without hypoventilation, characterized by sequences of periodic breathing that occurred in conjunction with myoclonic seizures. The majority of seizure-induced periodic breathing episodes were observed during a one-hour period of NREM sleep near the end of the study. Stereotyped epileptiform activity occurred in conjunction with a resumption of hyperventilatory respirations following apneic events. The increased respiratory drive, however, did not appear to be clinically epileptic in nature as the epileptiform activity either preceded or trailed the respirations. A variable REM and then NREM predominance of central events on successive polysomnograms further suggests that his central events are not intrinsic but that they are precipitated by epileptiform activity. Zonisamide, an anticonvulsant with carbonic anhydrase inhibitory properties was initiated and is being titrated to therapeutic goal. Conclusion: This case illustrates an unusual presentation of myoclonic seizure-induced periodic breathing during sleep. Support (If Any): Cincinnati Children's Research Foundation.